Interplay of resource endowments, agriculture and nutritional outcomes in the Central Indian Landscape - Padhan, Niranjan; Anantha, K.H.; Garg, Kaushal K.; Akuraju, V. R.; Singh, Ramesh; Jat, M.L. (Frontiers Media, 2025)
The agricultural development, resource availability and nutritional outcomes are inherently interconnected, particularly in ecologically vulnerable regions. In such context, fluctuations in resource endowments, especially water, directly impact agricultural productivity, which in turn shapes household income and food consumption patterns. Despite growing policy focus on improving agricultural output and food security, a fragmented understanding of how these domains interact has limited the effectiveness of interventions. This study, therefore, undertaken to bridge this knowledge gap by providing an integrated analysis of how natural resources and agricultural practices collectively influence nutritional outcomes in the Central Indian Landscape (CIL) in South Asia. A primary survey of 1,403 households was carried out from 20 villages across seven districts of the CIL and applied ordered probit model to identify important drivers which influences nutritional outcomes. On average, about 40% of total agricultural area was kept fallow either during monsoon or post-monsoon period largely due to poor water availability in dug wells, which is the major source of irrigation. For most crops, yield was ranged from 0.5 to 1.5 t ha−1. Livestock is an integral part of the farming system as 60% of the households own cattle, buffalo and goats. Income sources are diverse, with agriculture and livestock contributing significantly to large farmers’ income, while marginal and small farmers rely more on labor and remittances. The average annual household income for marginal farmers and large farmers is US$ 1,240 and US$ 4,930, respectively. A model analyzing factors influencing nutritional indicators such as energy, protein, and iron intake reveals that larger landholdings, higher income, education, and participation in welfare programs like Mahatma Gandhi National Rural Employment Guarantee Act (MGNREGA) improve nutritional outcomes. Family size negatively impacts dietary intake, while irrigated land positively affects energy, protein, and iron intake. These findings suggests that the critical need for integrated water resource management along with improving irrigation infrastructures, climate-resilient agriculture practices and promoting education and expanding access to social welfare programs are key to enhancing income, food and nutritional security of resource-poor households in vulnerable ecologies.